Acts of the General Assembly of the State of South Carolina (Columbia, SC: Julian A. Selby, 1866), at 14-15, §§ 34-44 - (:unkn) unknown (General Publisher, 1865)
Prohibited any “[p]ersons of color” from being a part of the militia and from keeping a firearm, sword, or other military weapon without permission.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES